2016
DOI: 10.1186/s12967-016-1067-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects by periodontitis on pristane-induced arthritis in rats

Abstract: BackgroundAn infection-immune association of periodontal disease with rheumatoid arthritis has been suggested. This study aimed to investigate the effect of pre-existing periodontitis on the development and the immune/inflammatory response of pristane-induced arthritis.MethodsWe investigated the effect of periodontitis induced by ligature placement and Porphyromonas gingivalis (P. gingivalis) infection, in combination with Fusobacterium nucleatum to promote its colonization, on the development of pristane-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…For the qPCR analysis of subgingival plaque samples, two sets of primers were used for bacteria detection, one species-specific pair for P. gingivalis and the other pair targeting the bacterial 16S rRNA gene [34,35]. The qPCR analyses were performed as described in the Supplementary Methods (Quantitative Polymerase Chain Reaction, qPCR).…”
Section: Methodsmentioning
confidence: 99%
“…For the qPCR analysis of subgingival plaque samples, two sets of primers were used for bacteria detection, one species-specific pair for P. gingivalis and the other pair targeting the bacterial 16S rRNA gene [34,35]. The qPCR analyses were performed as described in the Supplementary Methods (Quantitative Polymerase Chain Reaction, qPCR).…”
Section: Methodsmentioning
confidence: 99%
“…Using models of arthritis in rats, periodontitis induced by P. gingivalis had no effect in the development or severity of pristane-induced arthritis in Dark Agouti rats [143]. More recently, however, one study showed that P. gingivalis -associated periodontitis was sufficient to induce erosive arthritis in Lewis rats, providing the first direct evidence that P. gingivalis may have the capacity to induce arthritis [144].…”
Section: P Gingivalis In Ra Pathogenesismentioning
confidence: 99%
“…Several mechanisms have been proposed by which P. gingivalis may promote autoimmune arthritis in humans and in experimental animals. These include the induction of a systemic Th17 cell response [132,133,134], induction of autoantibodies [131,138,143,144], cross-reactivity between bacterial and host antigens [145], by promoting C5a generation [141], through direct dissemination of P. gingivalis into the joints [136], and by swallowing the bacteria, which may alter the gut microbiota and gut immune system [137]. Nevertheless, the production of citrullinated autoantigens by a PAD enzyme released from P. gingivalis is considered the most important mechanistic evidence to support a role of P. gingivalis in RA pathogenesis [14,146].…”
Section: P Gingivalis In Ra Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontitis was induced in the rats using standard procedures [15]. The rats were anesthetized via intraperitoneal administration of 50 mg/kg bwt pentobarbital and a suture was made around each cervix of the first molar (M1) on bilateral sides in the maxilla in the open mouth, using Hashimoto's gag.…”
Section: Preparation Of Rat Model Of Periodontitismentioning
confidence: 99%